Evaluation of hierarchical management of operating room nurses to in the promotion of high-quality nursing service (手术室护士分层管理在优质护理服务中的应用效果) - LI Yanzhen (李棪臻); ZHANG Hui (张慧); HE Lili (何利利); ZHANG Jing (张静); LEI Dan (雷丹); WEI Qianqian (卫倩倩); XI Hongna (席红娜); LI Hao (李豪); LIU Ruzhong (刘儒忠); HUANG Xinkun (黄新坤); LIU Xiongtao (刘雄涛) (中西医结合护理)
Objective To explore the application of hierarchical management of operating room nurses in the promotion of high quality nursing service. Methods In this study, a retrospective before-after control study was adopted, and 80 operating room nurses from January 2022 to December 2023 were selected as the research subjects. A hierarchical management model had been adopted science January 2023, and nurses were divided into N4, N3, N2, N1, and N0 levels, according to their seniority, professional title, educational background, and work experience. The operation skills of nurses before and after the hierarchical management were compared and analyzed, and satisfaction of intern students and surgeons with operating room nurses were evaluated. The occurrence of adverse nursing events during the operation and number of nurses participated in clinical research were analyzed. Results The implementation of hierarchical management had improved the test outcomes of nurses in surgical practice. There was an improved satisfaction with clinical teaching among nursing students and improved satisfaction with nursing among surgeons. In terms of adverse nursing events, 12 cases of insufficient surgical instruments and 12 cases of omission of nursing were reported before implementation of hierarchical management, and it dropped to 6 cases and 4 cases after implementation of hierarchical management. The number of people participating in the publication of scientific research papers and fund applications had increased after implementation of hierarchical management. Conclusion Hierarchical management of operating room nurses to helps to promote the high-quality nursing practice in surgical nursing. (目的 探讨手术室护士分层管理在优质护理服务中的应用效果。方法 2022年1月—2023年12月西安交通大学第二附属医院手术室共有临床护士80人。2023年1月开始实施护士分层管理, 综合护士的年资、职称、学历、工作经验等对护士进行分层管理, 观察2022年1月—12月和2023年1月—12月操作技能考核情况、实习学生和医师对手术室护士的满意度、术中不良事情的发生情况以及护士参与科研情况。结果 手术室实施护士分层管理后, 手术室护士的操作考试成绩提高; 医生及实习学生对手术室护士的满意度提升。2022年1月—12月发生的不良事件包括术中所用器械功能不全12例、护理记录遗漏12例; 2023年1月—12月发生的不良事件包括术中所用器械功能不全6例、护理记录遗漏4例。2023年1月—12月手术室护士参与科研立项人数和论文发表人数较2022年1月—12月上升。结论 手术室开展护士分层管理有助于提高优质护理服务质量。)